Impact of gastrointestinal endoscopy on HIV-infected children - Ukarapol N. (2014)
Objective: To evaluate the role of gastrointestinal (GI) endoscopy in human immunodeficiency virus (HIV)-infected children with GI problems. Methods: From 1998 to 2002, we retrospectively reviewed all cases of HIV-infected children presenting with GI problems in which an upper or lower GI endoscopy was indicated. The initial diagnostic endoscopic examination and any repeat endoscopic session leading to a new diagnosis were used in the data analysis. Tissue biopsies were obtained from all abnormal lesions and representative sites of normal-appearancing GI mucosa. Results: Fourteen patients (median age: 22.5 months) underwent 23 sessions of GI endoscopy, including 10 esophagogastroduodenoscopy, nine colonoscopy and four flexible sigmoidoscopy. Chronic diarrhea was the most common indication, followed by lower GI bleeding, abdominal/retrosternal pain, dysphagia/odynophagia, and upper GI bleeding. Gross endoscopic abnormalities were observed in 78.3%; whereas histological inflammation and opportunistic pathogens were identified in 87% and 43.5%, respectively. Cytomegalovirus was the most common identified pathogen. Abnormal gross findings were significantly associated with histological inflammation and identification of pathogens (P = 0.006 and 0.046, respectively). Specific changes in medical management were made in 50% of cases as a result of endoscopic investigation. Conclusion: If non-invasive investigations for HIV-infected children with GI symptoms fail to establish a diagnosis, gastrointestinal endoscopy should be performed and often yields a positive result leading to changes in medical management.